Parking Information System Base on Internet of Things (IoT) - Ali Basrah Pulungan; Musfi Oktavianda; Hastuti Hastuti; Hamdani Hamdani (Jurnal Teknologi Informasi dan Pendidikan, 2020)
One of the technological developments in the transportation sector that we can encounter today is the parking service system. Currently the parking area in a building has started to use an automatic system in its operation, but the use of parking lots is still constrained or it is difficult to find an empty parking space around the parking area so it is less efficient and takes a long time to park the vehicle. This research was conducted to design and create a parking information system that can be identified by parking users who want to park their vehicles and monitor the parking area before entering the parking area. To see the availability of parking spaces before entering the parking area, you can monitor them via a Smartphone using a web-based application.